2017
DOI: 10.15761/ams.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of pulse electroplated gold films: SEM-EBSD studies

Abstract: This paper reports the effect of annealing at various temperatures on microstructure and microtexture of the gold films deposited onto SiO 2 /Si(100) substrate using pulsed electrodeposition (PED). The samples were annealed for 3 days at 850ºC and for 5 hours at 900ºC and 910ºC. The microstructure and thermal stability of the electrochemically deposited gold films before and after annealing was investigated using scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD) techniques. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…During the past two decades, the electron backscattered diffraction (EBSD) technique remains one of the most powerful techniques to study grain boundaries characteristics in thin films, which is carried out in the scanning electron microscopy (SEM) . This technique enables the study of large areas of the sample, but is limited by its spatial resolution, which extends to several tens of nanometers or microns .…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, the electron backscattered diffraction (EBSD) technique remains one of the most powerful techniques to study grain boundaries characteristics in thin films, which is carried out in the scanning electron microscopy (SEM) . This technique enables the study of large areas of the sample, but is limited by its spatial resolution, which extends to several tens of nanometers or microns .…”
Section: Introductionmentioning
confidence: 99%
“…However, by implementing annealing processes, and/or potential cycling, preferred orientation may be developed while still utilizing a low loading of Au. 34,36,[47][48][49] The synthesis of the chemically deposited nanoparticles on XC72R carbon produced a powder that was analyzed with XRD and TEM. X-ray diffraction peaks showed that the Au nanoparticles deposited onto Vulcan XC 72R presented peaks that aligned well with International Centre for Diffraction Data (ICDD) card (PDF# 00-066-0091) peak positions for Au and gave an average crystallite size of 8 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the long-range surface plasmon polariton (LRSPP) along an IMI layered structure is commonly applied for the waveguides or biosensors, particularly in the NIR regime . Another application of an IMI sensor is for the measurement of the change of the medium’s refractive index by detecting the shift of the SPR dip in the total internal reflection spectrum. In general, a postprocess of annealing for a deposited Au film can improve the sensitivity of these SPR sensors. However, several types of defects induced by the thermal annealing are usually observed, such as the bulges (blisters), solid state dewetting, and pinholes (voids). These induced defects are also related to the quality of the adhesion layer, the delamination of film, the local overheating, and Rayleigh instability. The preservation of the film integrity after the annealing is essential for the following fabrication of nanostructures via FIB milling.…”
Section: Introductionmentioning
confidence: 99%